Perspektif Etika Bisnis Islam Terhadap Manajemen Laba - Nurliza Lubis; Nurul Hayati Panjaitan; Haiqal Alif Ramadhani; Fahriani Astuti Sitepu (Ali Institute of Research and Publication, 2024)
This study's definition of earnings management is based on Schipper's view that earnings management is